The impact of climate and land use changes on nitrogen and phosphorus pollution in the Luhun Lake Basin, China - Yang, Xu; Qiu, Shike; Wang, Chao; Hao, Limin (Frontiers in Earth Science, 2024)
Introduction: Water is an important ecological factor, and non-point source pollution (NPSP) seriously affects water security. In recent years, NPSP has affected water security and human survival in China. Methods: The Luhun Lake Basin has been selected as an example region of Yellow River Basin (YRB) in China, and the trends and impacts of nitrogen (N) and phosphorus (P) has been quantitatively evaluated by using geographic information system (GIS), remote sensing (RS) and InVEST model. Results: The results show that (1) the arable land and water bodies decreased, while forest land, grass land, construction land and unutilized land increased in the 20 years. The average annual precipitation increased from the northeast to the southwest in the 20 years; (2) the N and P exports first increased in 2000–2010 and then decreased in 2010–2020, and finally increased in 2000–2020; (3) with the increase of precipitation, the N and P exports decreased in 2000–2010, 2010–2020 and 2000–2020; (4) the amount of N and P exports on arable land and construction land were more than that on the other land use types. The N and P exports on each land use type all first increased and then decreased, and the overall change trend all increased in 2000–2020. Discussion: This study demonstrates how geographic information system (GIS), remote sensing (RS) and InVEST model can be used to assess nitrogen and phosphorus pollution in data scarce regions.